Rum, Gin and Maize: Deities and Ritual Change in the Gold Coast during the Atlantic Era (16th century to 1850) - Emmanuel Akyeampong; Samuel A. Ntewusu (Afriques)
This paper examines the incorporation of rum and gin as powerful spiritual drinks in pre-colonial Gold Coast, particularly in the context of state formation and warfare, and the growing importance of maize, side by side with the indigenous yam, as the food of gods. Through food and drink, we analyze changing notions of spiritual efficacy and the ascendancy of war deities, and we interrogate how shifts in socio-political contexts aligned with those in the spiritual realm. Why were European liquors like gin, rum, and schnapps incorporated into ritual on the Gold Coast and not others? We juxtapose geographically dispersed ritual landscapes, contrasting the Atlantic coast and its immediate hinterland with a case study from the northern Guan in our endeavor to understand how far-reaching were Atlantic processes, as well as the “logic” of ritual transformation.